Pressure Load Characteristics of Explosions in an Adjacent Chamber - Chuan-hao Wang; Shu-shan Wang; Jing-xiao Zhang; Feng Ma (Shock and Vibration)
To learn more about dynamite explosions in confined spaces, we focused on the chamber adjacent to the main chamber, the main chamber being the location of the explosion. We investigated the characteristics of two damaging pressure loads: first reflected shock wave and quasistatic pressure. In this work, we analyzed the characteristics of the first reflected shock wave and the quasistatic pressure formed by the explosion of the chamber charge. Simulated chamber explosion experiments were carried out, where high-frequency piezoelectric sensors were used to measure the first reflected shock wave, and low-frequency piezo-resistive sensors were used to measure the quasistatic pressure. Valid and reasonable experimental data were obtained, and the experimental values of the pressure load were compared with those calculated from the classical model. The results showed that when the main chamber was partially damaged by the explosion load, the adjacent chambers were not subjected to the shock wave load, and the quasistatic pressure load was less than that in the main chamber. The presence of adjacent chambers did not affect the shock wave load in the main chamber. Using the mass of the explosive and the blast distance as input parameters, the internal explosion shock wave load parameters, including those in adjacent chambers, can be calculated. The presence of the adjacent chamber did not affect the theoretically calculated quasistatic overpressure peak in the main chamber. Using the mass of the explosive and the spatial volume of the chamber as input parameters, the quasistatic pressure load parameters of the internal explosion can be calculated, including those in the adjacent chambers.